Analisis Manuver Penyulang Selecta untuk Menjaga Nilai Keandalan Sistem Distribusi di PT. PLN (Persero) ULP Batu - Sukamdi; Awan Setiawan; Heri Sungkowo (Elposys: Jurnal Sistem Kelistrikan, 2022)
PT. PLN (Persero) ULP Batu, The Selecta feeder is one of the 7 feeders in the distribution system that supplies several areas in PT. PLN (Persero) ULP Batu. In the Selecta feeder themselves, the number of error that occurred from January to November 2020 was fourteen times, with details of one time temporary error and thirteen times permanent errors. Delegating a portion of the load from feeders which got error can have an impact on feeders which are working normally. This can cause a voltage drop on the feeder for maneuvering purposes so that the distribution of electric power becomes less than optimal and requires some other loads to be temporarily transferred to other feeders. Based on the problems that occur, it is necessary to analyze the maneuver to reduce the impact of disruption on The Selecta feeder and maintain the reliability value of the distribution system at PT. PLN (Persero) ULP Batu.